Urban revitalisation through lighting design - Björklund, Erika (2007)
Venice has a unique location in the Lagoon which dates back to the first century BC. It is thanks to this isolation that Venice has been able to evolve with success for centuries. Today, in contact with post-modern society, the former republic La Serenissima faces various problems. During the last 300 years, many changes have taken place to transform the original structure and use of the city. With the construction of the railway and road, which connects the archipelago to the mainland, access was made easier. The new link further meant an increase in tourism, a monoculture that is evident today when visiting the city. The steady reduction in population since the Second World War together with urban decay has meant that Venice feels like a museum of art and architecture. Historically, Venice was vivid but this former bustle can today only be traced during the day and in some parts of the city. An improved lighting system could encourage activity after dark, as well as it would improve the feeling of safety, enhance the aesthetic appearance of the city, reduce light pollution and save energy.